Autonomy and infant feeding decision-making among teenage mothers in a rural and urban setting in KwaZulu-Natal, South Africa - Ngcwalisa Amanda Jama; Aurene Wilford; Lyn Haskins; Anna Coutsoudis; Lenore Spies; Christiane Horwood (BMC, 2018)
Abstract Background The nutritional status of infants born to teenage mothers can be sub-optimal compared to those born to older mothers. One contributing factor is inappropriate feeding practices adopted by teenage mothers. Little is known about how infant feeding decisions are made among teenage mothers, particularly in under resourced settings. In this study we prospectively explored autonomy and infant feeding decision-making among teenage mothers in a rural and urban setting in KwaZulu-Natal, South Africa. Methods This study adopted a qualitative longitudinal design. Thirty pregnant participants were recruited to the study cohort, from the catchment area of two hospitals (one urban and one rural). Participants were purposively selected to include teenagers, HIV positive, and working pregnant women. We report findings from ten teenage mothers, aged between 15 and 19 years, who participated in the larger cohort (n = 5 rural; n = 5 urban). Monthly in-depth interviews were conducted with participating mothers for 6 months starting 2 weeks after delivery. All interviews were conducted in the local language, transcribed verbatim and translated into English. Data was coded using NVivo v10 and framework analysis was used. Results Findings from this study showed that teenage mothers had knowledge about recommended feeding practices. However, our findings suggest that these mothers were not involved in infant feeding decisions once they were at home, because infant feeding decision-making was a role largely assumed by older mothers in the family. Further, the age of the mother and financial dependency diminished her autonomy and ability to influence feeding practices or challenge incorrect advice given at home. Most feeding advice shared by family members was inappropriate, leading to poor infant feeding practices among teenage mothers. Returning to school and fear of breastfeeding in public were also barriers to exclusive breastfeeding. Conclusion Teenage mothers had a limited role in the infant feeding decision-making process. Health workers have an important role to play in ensuring that knowledge about infant feeding is shared with the mother's family where infant feeding choices are made. This will improve support for teenage mothers, and may also positively impact on the nutritional status of children.